Relationship Between Lifestyle And Hypertension In The Elderly In The Area Of The Upt Puskesmas Naga Kesiangan Regency Of Serdang Bedagai In 2021 - Ricard Fredrik Marpaung; Hotria Pinondang Siregar (Institute of Computer Science (IOCS), 2021)
Indonesia is a country that is entering the era of aging structured population because the population aged 60 years and over is around 7.18 % . One of the medical problems that often occurs in the elderly is hypertension, even in 2013 hypertension was the main disease of the 10 disease sequences in Indonesia (Kemenkes, 2013). Hypertension is a medical problem that often occurs in the elderly. Factors that can be controlled are lifestyle, including physical activity, diet, rest habits and smoking history. This study aims to determine the relationship between lifestyle and the incidence of hypertension in the elderly at the UPT Puskesmas Naga Kesiangan, Serdang Bedagai Regency. This study used a cross sectional design with 47 respondents who were taken using purposive sampling technique. Data was collected by using a questionnaire and measuring blood pressure. The results of the chi-square analysis showed that there was no relationship between lifestyle smoking, drinking coffee and resting with the incidence of hypertension with p value > 0.05, while there was a lifestyle relationship between diet and physical activity obtained with p value < 0.05. . Suggestions for health care workers to be more proactive in providing counseling about healthy lifestyles and conducting regular visits to observe directly the implementation of a healthy lifestyle.